Pengaruh Ukuran Perusahaan, Kebijakan Hutang dan Profitabilitas Terhadap Nilai Perusahaan Pada PT Gudang Garam Tbk Periode 2010-2021 - Asep Muhammad Lutfi (Ekonomis: Journal of Economics and Business, 2022)
This study aims to analyze the effect of the firm size ratio, debt policy ratio  and profitability ratio on the firm value ratio at PT Gudang Garam Tbk. The data used in this study is secondary data from the company's financial statements from 2010–2021. The methodology used is classical assumption test, simple linear regression analysis, multiple linear regression analysis, determinant coefficient and hypothesis testing. Based on the test results, firm size and debt policy have no partial effect on firm value, profitability has a partial effect on firm value, firm size, debt policy and profitability has a simultaneous effect on firm value. The results of the R2 test show that Company size, debt policy and profitability have an influence of 69% on Firm Value while the remaining 31% is influenced by other factors. which means that there is no effect of Firm Size, Debt Policy and Profitability will reduce Firm Value of 38,809. In this case, the increase in Firm Size, Debt Policy and Profitability will have a positive effect on Firm Value. From the results of the T-Test Firm Size and Debt Policy have no partial effect on Firm Value, Profitability has a partial effect on Firm Value. From the results of the F test, firm size, debt policy and profitability have a simultaneous effect on firm value.